Effect of Supplementation of Tinospora cordifolia (at Graded Levels) and Ascorbic Acid on Nutrient Metabolizability and Feed Passage Rate of Broiler Chickens - Jain, D.; Dhuria, R. K.; Sharma, T.; Bothra, T. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted September to October, 2016 to investigate the effect of Tinospora cordifolia (at graded levels) or ascorbic acid alone and in combinations on nutrient metabolizability and feed passage rate using 360 one day old broiler chicks. The experiment was done in 5×2 factorial experiment within a completely randomized design and divided into ten dietary treatments groups (T1–T10) in triplicate of 12 chicks/replicate. Following a 6-week feeding trial, five days metabolic trial was carried out at the Experimental Poultry Unit, located in poultry farm of College of Veterinary and Animal Science, Bikaner. The average temperature (31oC) during the study period was higher than the recommended normothermia zone i.e. 22–28°C established for poultry, which showed that birds were in chronic heat stress. The metabolizability (%) of all nutrients remained non-significant due to interaction (Giloy×Ascorbic acid) effect. Further, due to effect of Giloy only the metabolizability (%) of crude protein showed significant effect, while due to effect of ascorbic acid only metabolizability (%) of dry matter showed significant effect.Chronic heat stress in present study showed negative effect on nutrient metabolizability and feed passage rate in control group as compared to various treatment groups. Improvement in nutrient metabolizability and feed passage rate was observed due to supplementation of Giloy (Tinospora cordifolia) or ascorbic acid alone and their various combinations in broiler feeding. It was concluded that supplementation of Tinospora cordifolia (Giloy) at 0.25% level with ascorbic acid @ 0.025% may be as a beneficial management strategy in poultry feed during chronic heat stress.